1983
DOI: 10.1007/bf02214905
|View full text |Cite
|
Sign up to set email alerts
|

The excretion of campylobacter, salmonellae andGiardia lamblia in the faeces of stray dogs

Abstract: Faecal samples were collected from impounded stray dogs, classified as under or over six months of age, on their arrival in kennels and again 5-7 days later. The faeces were examined for the presence of campylobacters, salmonella and Giardia lamblia. No significant difference was found in the rate of isolation of these organisms between the two age groups. There was, however, a significant increase in the rate of isolation at days 5-7 compared with day 1. It is suggested that while dogs may acquire campylobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Furthermore these findings relate to pathogenic salmonellae, since culture collections contained clinical isolates associated with disease in either humans or dogs. In dogs those associated with clinical infections may represent only a proportion of salmonellae, since carriage without clinical signs of infection and sub-clinical shedding is also reported to varying extents [ 2 , 10 , 11 , 55 ]. In fact, the prevalence of Salmonella in healthy dogs and cats in some populations may be similar to that in diarrheic animals [ 56 , 57 ] with incidence rates reportedly differing across geographies [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore these findings relate to pathogenic salmonellae, since culture collections contained clinical isolates associated with disease in either humans or dogs. In dogs those associated with clinical infections may represent only a proportion of salmonellae, since carriage without clinical signs of infection and sub-clinical shedding is also reported to varying extents [ 2 , 10 , 11 , 55 ]. In fact, the prevalence of Salmonella in healthy dogs and cats in some populations may be similar to that in diarrheic animals [ 56 , 57 ] with incidence rates reportedly differing across geographies [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of canine giardiasis in the east of Scotland has been reported to range from 4 to 9-9 % [7,8]. Two studies from the south-east of England found between 14 5 and 20 % of dogs infected [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Dogs have been reported to harbour and shed Salmonella subclinically. High numbers of the microorganism can reside in the intestines and mesenteric lymph nodes without clinical signs [ 22 ] making an estimate of the prevalence of salmonellae in dogs in the community difficult to establish. The prevalence of subclinical carriage of Salmonella in clinically healthy dogs varies greatly among individual countries and has been reported to range from 0 to 44 % [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%